Relationship between Caregivers’ Beliefs about Medications and Medication Adherence in Children and Adolescents with Epilepsy - Eshghi, Fateme; Badri, Shiva; Bostani, Sanaz; Rafati, Shideh; Hosseini, Meimanat (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Children with epilepsy need sustained drug treatment to achieve optimal and desired health outcomes. However, non-adherence to drug treatment is a common cause of adverse health outcomes in this population. This study aimed to investigate the relationship between caregivers’ beliefs about antiepileptic drug therapy and adherence to medication in children and adolescents with epilepsy. Methods: This correlational and cross-sectional study was conducted on 151 caregivers of children and adolescents with epilepsy aged between 2 months and 19 years old referred to the neurology clinic for epilepsy in Children’s Hospital of Bandar Abbas, Iran. Data collection tools included demographic and general questionnaires; the Medication Adherence Report Scale (MARS) to assess medication adherence and the Beliefs about Medication Questionnaire (BMQ) for assessing the pharmaceutical beliefs of caregivers. Results: Using quantile regression, there was no significant relationship between medication adherence and caregiver belief in the necessity of medications to control a child’s epilepsy (P=0.38) and concern about the medications’ side effects and efficacy (P=0.24). However, 47.7 % of caregivers reported full medication adherence. Conclusions: Education about awareness of how to use and the effects of antiepileptic drugs is essential. By taking these actions, it is expected to increase medication adherence and following this, more appropriate control of epilepsy in children and adolescents.